Clinical Features and Prognostic Risk Prediction of Non-Hodgkin Lymphoma-Associated Hemophagocytic Syndrome - Yao, Shuyan; Jin, Zhili; He, Lingbo; Zhang, Ruoxi; Liu, Menghan; Hua, Zhengjie; Wang, Zhao; Wang, Yini (Frontiers in Oncology, 2021)
Background. Malignancies, especially lymphoma, are a common cause of adult secondary HLH and an independent risk factor for the prognosis of HLH patients. Methods. Patients with lymphoma alone or concurrent lymphoma-associated phagocytic syndrome (LAHS) admitted to Beijing Friendship Hospital from January 2016 to December 2020 were enrolled in this study. Findings. There were 348 lymphoma patients, 104 concurrent with LAHS. The pathological type of lymphoma without LAHS was dominated by B-cell lymphoma, while those with LAHS were T/NK-cell lymphoma predominantly (p<0.001). Superficial lymph node enlargement was more significant in patients with B-LAHS (p=0.006), while patients with T/NK-LAHS had lower neutrophil counts (p=0.005), lower fibrinogen levels (p<0.001), higher transaminase levels and more co-infection with EBV (p<0.001). B-LAHS had significantly higher IL-10 levels than with T/NK-LAHS (p=0.006), and NK/T-LAHS had significantly higher IP-10 levels than other T-LAHS (p=0.008). Age, platelets count, IPI, history of NK/T lymphoma and no remission of HLH were independent risk factors for prognosis in patients with non-Hodgkin lymphoma-associated phagocytic syndrome (NHL-LAHS), and a prognostic risk score model for NHL-LAHS was developed. Conclusion. LAHS is a life-threatening disease with a poor prognosis. The prognostic risk score model for NHL-LAHS with a good fit and validation for the test has value for clinical application.